2019
DOI: 10.1038/s42003-019-0502-7
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive colour change and background choice behaviour in peppered moth caterpillars is mediated by extraocular photoreception

Abstract: Light sensing by tissues distinct from the eye occurs in diverse animal groups, enabling circadian control and phototactic behaviour. Extraocular photoreceptors may also facilitate rapid colour change in cephalopods and lizards, but little is known about the sensory system that mediates slow colour change in arthropods. We previously reported that slow colour change in twig-mimicking caterpillars of the peppered moth ( Biston betularia ) is a response to achromatic and chromatic visual c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…Color change resulting from changing pigment and/or structure occurs in some insects. In caterpillars of the peppered moth, the adjustment of body color to the background is guided by an opponent mechanism (34). In other Lepidoptera, pupal color is controlled by the light environment experienced as prepupa but is likely controlled by light intensity rather than color (54).…”
Section: Camouflage or Body Colorationmentioning
confidence: 99%
“…Color change resulting from changing pigment and/or structure occurs in some insects. In caterpillars of the peppered moth, the adjustment of body color to the background is guided by an opponent mechanism (34). In other Lepidoptera, pupal color is controlled by the light environment experienced as prepupa but is likely controlled by light intensity rather than color (54).…”
Section: Camouflage or Body Colorationmentioning
confidence: 99%
“…Immature lepidopterans can perceive visual, gravitational, and olfactory stimuli, all of which could be used by both feeding larvae and pre-pupae to orient themselves within their respective habitats. Caterpillars perceive light through stemmata (simple eyes) located on the head (Gilbert, 1994;Stehr, 2009b;Chapman, 2012), as well as extraocular photoreceptors located in the skin (Eacock et al, 2019). Color and light intensity can be used by larvae to locate a host plant (Kandori et al, 2015), or by prepupae to locate a pupation site (Wiklund, 1972;Roden et al, 1992;Veldtman et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Matching habitat choice has received considerable research attention in the last decade and, although several tests have been conducted under controlled indoor conditions [32][33][34], examples of phenotype manipulation experiments are restricted to a couple studies on grasshoppers. For example, in a series of laboratory experiments using a mosaic of solar radiation, Karpestam et al [30] and Wennersten et al [31] showed that pale-painted and dark-painted grasshoppers tended to settle in the thermal zone offering the better fitness prospects given their susceptibility to radiation.…”
Section: Introductionmentioning
confidence: 99%